Dampak Tren Hijab Terhadap Relasi Suami Istri - Sari, Yuli Kartika; Nuraida; Muzaiyanah (Pubmedia Social Sciences and Humanities, 2024)
This research discusses the hijab trend which is increasingly widespread and can be found anywhere, this research was conducted in Mesuji Jaya Village, District. Mesuji Jaya District. Ogan Komering Ilir. The problem in this research is that there are many hijab trends that are widespread and can be found not only in traditional markets but can be found throughout social media such as Facebook, Instagram, TikTok, online shops and so on, so they have an impact on husband and wife relationships. The aim of this research is to determine the impact of the hijab trend on husband and wife relationships. Data collection tools include interviews, observation and documentation. This research uses qualitative research, namely research that uses a natural setting with the aim of interpreting phenomena that occur and is carried out using various existing methods. So, the data from this research was taken and obtained directly from original sources (not through intermediaries), the data sources in this research were divided into two, namely the first primary data source which was obtained directly from interviews conducted offline and online, while secondary data used as a complement to this research, for example pictures, tables, charts, researchers' data documents. From this research it can be concluded that the impact of the hijab trend on husband and wife relations has two impacts, namely positive and negative impacts. The positive impact can be seen from two aspects, namely the physical aspect (body image component) and the psychological aspect (self-esteem component and role component) in this case it can be seen by the increasingly widespread hijab trend then wives use the hijab to beautify themselves, to maintain The self-esteem and honor of herself and her husband is then done to prove the loyalty, obedience and cooperation carried out by the wife in order to create a harmonious relationship. The negative impact can be seen from the economic aspect where wives tend to be wasteful when managing household finances in order to fulfill their own egos.